Hubungan Antara Kepercayaan Diri dengan Tingkat Kecemasan Menghadapi Pertandingan Atletik di Jawa Tengah - Risky Bagas Sadzali; Wahyu Endang Styowati; Betie Febriana (Jurnal Ventilator, 2025)
Self-confidence and anxiety are the main factors that affect an athlete's performance during a match. High self-confidence has a positive impact on an athlete's ability to focus, control themselves, and perform optimally, while high anxiety tends to decrease an athlete's concentration, stamina, and performance. Data shows that many athletes in Indonesia experience anxiety before a match, which significantly affects their performance. Therefore, efforts to increase self-confidence and reduce anxiety levels are very important to help athletes perform optimally, achieve achievements, and bring pride to the nation. Quantitative research type with cross sectional approach. The sample used was 17-year-old athletes who participated in the 2024 Bahurekso Cup. The technique used in sampling was total sampling of 109 respondents. The correlation test used in this study was uci chi square. The results of the study using the Chi Square test obtained a p value = 0.000 (p <0.05) which means that there is a relationship between self-confidence and anxiety levels in athletes when facing matches. There is a close relationship between self-confidence and anxiety levels in facing athletic matches in Central Java.